Analisis Potensi Penerimaan Pajak Kendaraan Bermotor di Masa Pandemi (Studi Kantor SAMSAT Kota Bekasi 2019-2021) - Yumna Amelia; Irawati Irawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Background: The rapid increase of the number of motorized vehicles should be able to increase the potential for motor vehicle tax revenues. However, for the last 3 years, the motorized vehicle revenues in Bekasi City experienced a decline. Objective: This study aims to identify and analyze the potential for motor vehicle tax revenues during the pandemic (study at the Bekasi City SAMSAT Office in 2019-2021), the obstacles that arise, and efforts to overcome these obstacles. Methods: This research was conducted at the Bekasi City SAMSAT Office using descriptive qualitative research methods Results: Data was collected through observation, interviews and documentation. The results of the study show that the collection of motor vehicle taxes during the 2019-2021 pandemic in Bekasi City was quite good, but the exploration of potential was not maximized. In 2019 the realization of motor vehicle tax revenues reached Rp 1,129,312,381,500 or 100.71% and in 2020 it decreased to Rp 1,046,676,391,950 or 78.06%, not achieving the target. In 2021 the realization of motor vehicle tax revenues increased to Rp. 1,133,416,073,950 or 104.16%. The potential for motor vehicle tax revenues in the last 3 years has not been maximized due to the Covid-19 pandemic. To overcome these obstacles, several efforts need to be made, such as conducting tax amnesty programs and tax campaigns as well as improving the quality of service for taxpayers